The Creation of the ABC Studio Orchestras, 1935–1945. Issue 1 (2nd January 2022) - Morgan, Kenneth
Abstract: This article analyses the creation of studio orchestras by the Australian Broadcasting Commission (ABC) as part of a policy of musical federalization. The orchestras were created in the decade after 1935 in all six Australian states, and later expanded to form state symphony orchestras for radio broadcasting and for public performances in concerts. The article argues that the combined effort of a group of men appointed to managerial and controller positions in the ABC was responsible for the oversight of the founding of the studio orchestras; that they spread the available musical talent across the six states; and that they succeeded in their attempt to stimulate public demand for listening to orchestras on radio by paying close attention to the musical capabilities of conductors and thorough auditioning of players joining the orchestras. Within a decade after their foundation, the studio orchestras became permanent ambassadors for the programming of live classical music on the ABC's radio stations.